2021
DOI: 10.3390/met11050805
|View full text |Cite
|
Sign up to set email alerts
|

AA7075-ZrO2 Nanocomposites Produced by the Consecutive Solid-State Process: A Review of Characterisation and Potential Applications

Abstract: Solid-state recycling is a direct conversion method for producing metal chips, whereas the materials are plastically deformed into the final product without melting, offering lower energy consumption and metal waste. This technique was reported for fabricating aluminium-zirconium oxide (Al-ZrO2) composite and it was widely used to avoid metal chips bounding at high temperatures during the extrusion process. Aluminium alloy (AA7075) is known for its high yield strength of more than 500 MPa under optimum ageing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…Borblik et al [19] proposed that the decreases in the size of sample resulted in decreases in all characteristics of the material surface. Luce et al [20] reported the use of AFM to analyse sizes and other important characteristics for surface topography with ease in Materials 2021, 14 Borblik et al [19] proposed that the decreases in the size of sample resulted in decreases in all characteristics of the material surface. Luce et al [20] reported the use of AFM to analyse sizes and other important characteristics for surface topography with ease in Materials 2021, 14 Borblik et al [19] proposed that the decreases in the size of sample resulted in decreases in all characteristics of the material surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Borblik et al [19] proposed that the decreases in the size of sample resulted in decreases in all characteristics of the material surface. Luce et al [20] reported the use of AFM to analyse sizes and other important characteristics for surface topography with ease in Materials 2021, 14 Borblik et al [19] proposed that the decreases in the size of sample resulted in decreases in all characteristics of the material surface. Luce et al [20] reported the use of AFM to analyse sizes and other important characteristics for surface topography with ease in Materials 2021, 14 Borblik et al [19] proposed that the decreases in the size of sample resulted in decreases in all characteristics of the material surface.…”
Section: Discussionmentioning
confidence: 99%
“…Luce et al [20] reported the use of AFM to analyse sizes and other important characteristics for surface topography with ease in Materials 2021, 14 Borblik et al [19] proposed that the decreases in the size of sample resulted in decreases in all characteristics of the material surface. Luce et al [20] reported the use of AFM to analyse sizes and other important characteristics for surface topography with ease in Materials 2021, 14 Borblik et al [19] proposed that the decreases in the size of sample resulted in decreases in all characteristics of the material surface. Luce et al [20] reported the use of AFM to analyse sizes and other important characteristics for surface topography with ease in sample preparation for nano or microscales of the magnetic thin films.…”
Section: Discussionmentioning
confidence: 99%
“…The observed phenomenon can be attributed to various factors, such as a heightened rate of work hardening, the development of dislocation tangles around the particles, a consistent distribution of reinforcement, and plastic incongruity between the reinforcement and matrix [45][46][47][48]. Zirconium Oxide also improved the exural strength of composite when it is added in different wt.% into the composite [49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…The SSR by hot extrusion resulted in high strength enhancement of the processed chips due to severe deformation induced during extrusion [6][7][8]. In addition, SSR by hot extrusion could be cost effective compared to other conventional concepts of material recovery, saving 40% of materials, 31% of energy, and 60% of labour [9,10].…”
Section: Introductionmentioning
confidence: 99%